2021
DOI: 10.1371/journal.pone.0238137
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid mental disorders and quality of life of people with epilepsy attending primary health care clinics in rural Ethiopia

Abstract: Background Evidence from high-income countries demonstrates that co-morbid mental disorders in people with epilepsy adversely affect clinical and social outcomes. However, evidence from low-income countries is lacking. The objective of this study was to measure the association between co-morbid mental disorders and quality of life and functioning in people with epilepsy. Methods A facility-based, community ascertained cross-sectional survey was carried out in selected districts of the Gurage Zone, Southern E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…It has been shown that the numbers and doses of ASMs can modulate the seizure frequency and effects on the QOL to cause multiple psychological disorders like abnormal behavior, stigma, physical impairments, or other mental co-morbidities like social, behavioral, physiological, or psychological well-being. In a study, stigma was found to be associated with seizure severity and it showed a poorer quality of life [ 19 , 20 ]. The effect of ASMs in PWE resulted in a worse quality of life due to enriched seizure episodes, adverse effects, psychological issues, and various etiological aspects that may lead to medical co-morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the numbers and doses of ASMs can modulate the seizure frequency and effects on the QOL to cause multiple psychological disorders like abnormal behavior, stigma, physical impairments, or other mental co-morbidities like social, behavioral, physiological, or psychological well-being. In a study, stigma was found to be associated with seizure severity and it showed a poorer quality of life [ 19 , 20 ]. The effect of ASMs in PWE resulted in a worse quality of life due to enriched seizure episodes, adverse effects, psychological issues, and various etiological aspects that may lead to medical co-morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Neither the primary health care facility nor the PHC workers are equipped with this skill or resource. The low detection of anxiety disorders in this study could also be due to the presentation of depression in Ethiopian culture, which tends to be a combination of anxiety, somatic and depressive symptoms rather than typical DSM criteria, alongside the non-biomedical causal attributions of depressive/anxiety symptoms in this society [ 27 ]. It is possible that psychiatry nurses tended to prioritise a diagnosis of depression over anxiety disorders as this reflected their experince of presentation in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The total mean score ranges from 0-100 with a higher score indicating better quality of life. For this study, the instrument was adapted and construct validity was established (30).…”
Section: Primary Outcome (T 0 and T 1 )mentioning
confidence: 99%